Synthesis of Mesoporous LTA Zeolite with Bridged Silsesquioxane as Template - Liu, Hong-Tao; Song, Guo-Qiang; Meng, Ying; Li, Fu-Xiang (Asian Journal of Chemistry, 2014)
In this paper, a mesoporous LTA zeolite with uniform intracrystal mesopores has been synthesized using the bridged silsesquioxane with three hydrolyzable methoxy silicon groups as the template, which can form Si-O-Si covalent bonds with the zeolite structure in undergoing nucleation. The structural and textural properties were characterized by X-ray diffraction, nitrogen adsorption, scanning electron microscopy and transmission electron microscopy. The XRD patterns of the as-synthesized samples clearly indicated a gradual decrease in the size of the crystalline domains as the amount of the template increases. The samples all showed a type IV N2 adsorption-desorption isotherm characteristic of mesoporous materials and the pore size distribution centered at around 3.401-3.799 nm, confirming the presence of uniform intracrystal mesopores in the zeolite samples. SEM and transmission electron microscopy observations of the samples showed that the uniform and partially interconnected intracrystal mesopores randomly distributed throughout the globular particles with rugged surfaces.